Proceso de atención de enfermería en un recién nacido a termino con exposición perinatal al VIH. - Guiracocha Jiménez, Carlos Alfonso (2020)
Infection by the human immunodeficiency virus (HIV) plays a very fundamental role for health worldwide. Most cases of pediatric infections basically originate from vertical transmission through an HIV-positive pregnant woman. The infection can be carried out during pregnancy with a percentage of 60-70%, in breastfeeding with 30-40% and by intrauterine transmission with 30-40% (Chavez, 2016). It is vitally important to know that within the clinical manifestations we find the delay in growth and psychomotor development, the frequency of nonspecific manifestations of disease, among others. However, treatment is universally indicated and must be monitored, since the main objective is to ensure that it is capable of controlling viral replication and that it does not produce any type of short-term and long-term toxicity (Chavez, 2016). The nursing process was developed in a newborn with a diagnosis of perinatal exposure to HIV with the sole objective of contributing to improve their health status through physical assessment and functional patterns, using the Marjory Gordon model to be able to prioritize the nursing interventions and thus develop and execute a specific care plan according to the needs required by the patient, using the NANDA, NIC and NOC taxonomy.